The Battle of Bataan a complete history - Young, Donald J. 1930-; EBSCOhost eBook Collection (Jefferson, N.C. McFarland, 2009)
"This book begins with an overview of the Philippine, American, and Japanese forces which fought on Bataan, followed by chapters looking at the military buildup, the counterattack in the II Corps and the withdrawal from Abucay, the Japanese invasion, the Battle for the Points, the Battle of the Pockets, and, finally, the surrender and the death march"--Provided by publisher.
Military organizations and designations -- Introduction -- The battle is joined -- Counterattack and withdrawal -- Invasion from the sea -- The Battle for the Points continues -- The Battle of the Pockets -- "We spit on our hands and waited" -- Beginning of the end -- No gleam of victory -- Bataan's last hours -- "Bataan has fallen" -- Appendix A: 192nd and 194th tank battalions; Bataan artillery and antiaircraft; Bataan engineers and quartermaster; The Bataan hospitals and the medical situations; Communications -- Appendix B: Refugees; Troop morale; The weather and its effect.
Electronic reproduction.
Keywords: Bataan, Battle of, Philippines, 1942.; Electronic books